The internal and external impact on Moroccan-Iranian relations (Journal of the College of Basic Education, 2022)
Morocco is keen, based on its adherence to its Arab and Islamic identity, to build a strong relationship with Islamic countries, and the geographical distance of the Maghreb region from the Arab Gulf and from the depth of the Arab and Islamic world has made the political class in Morocco immune from all fears that govern many Arab regimes in the Gulf towards the Republic. Iranian Islamic